La justification morale dans le débat public - Gilles Gauthier (Communication)
The article deals with the use of moral justification in public debates. The question is approached from the point of view of argumentation. An invitation in 2005 to former French Prime Minister Alain Juppé, as visiting professor at the École Nationale d’Administration Publique, in Québec City, spurred a heated debate among university professors. Two opposing arguments were developed : one centred on trust in public administration, the other on the moral obligation of universities. The analysis of this debate reveals basic flaws in both arguments.